A process for improving the properties of concrete

CN117923845BActive Publication Date: 2026-10-27JILIN INST OF WATER RESOURCES SCI +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410097864.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-24
Publication Date
2026-10-27
Estimated Expiration
2044-01-24

AI Technical Summary

Technical Problem

[0004]上述一种混凝土的生产工艺及混凝土,通过改变骨料与水泥的添加顺序,提高外加剂的利用率,但产出的混凝土内会含有大量孔隙,不但使混凝土的强度下降,而且容易渗入雨水,腐蚀混凝土内部

Benefits of technology

[0014]在常温和中温环境下,微孔刚玉球会和磷酸二氢盐发生聚合反应,使混凝土强度增强,同时不会发生严重的脱水分解和物相的转化导致混凝土结构破坏,因此使混凝土具有较好的耐热性,在较大温度范围内保持有良好的热态强度,同时冷态强度也不会明显的下降。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117923845B_ABST
    Figure CN117923845B_ABST
Patent Text Reader

Abstract

The application discloses a kind of processes for improving the performance of concrete in the field of concrete preparation, comprising the following steps: preparation of strong penetrant: fluorosilicate, polycarboxylate water reducing agent, complex soluble calcium salt, alcohol amine enhancer, polymeric amide solubilizer, hydrated calcium silicate gel powder and water are mixed and stirred;Preparation of concrete: the raw materials of concrete include cement, stone, fine river sand, slag, microporous corundum ball, alumina micropowder, dihydrogen phosphate, water and admixture, first water is mixed with stone, fine river sand and slag, after stone, fine river sand, slag and microporous corundum ball are filled with water, cement, alumina micropowder, dihydrogen phosphate and admixture are mixed and stirred, step three: strong penetrant modification: when using concrete construction, first spread concrete, when concrete, spray strong penetrant to the surface of concrete again.The technical scheme of the application can reduce the number of pores generated by concrete and enhance the strength of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete preparation, specifically a process for improving concrete performance. Background Technology

[0002] Concrete is a widely used building material with advantages such as abundant raw materials, low price, simple processing, high strength, and good durability. Concrete is mainly composed of cement, water, aggregates, and powders mixed in a certain proportion. Aggregates include coarse aggregates such as crushed stone and fine aggregates such as sand, while powders include mineral admixtures. To adjust and improve the performance of concrete, various admixtures with different properties are usually added to optimize the concrete formula. Currently available concrete admixtures can reduce mixing water, increase workability, control setting time, provide early strength, enhance strength, improve durability, stain, and entrain air. In current concrete production processes, aggregates and powders are usually mixed first, and then admixtures are added to water and the resulting mixture. In this process, when the aggregates come into contact with water containing admixtures, they absorb a large amount of water, and simultaneously absorb the admixtures mixed in the water, resulting in a reduction in the usable amount of admixtures and thus lowering their utilization rate.

[0003] To address the aforementioned problems, patent publication number CN110156389B discloses a concrete production process and concrete, comprising the following preparation steps: a) taking water accounting for 65%-75% of the total weight of water used, mixing it with aggregates to obtain mixture A; b) adding powder to mixture A and mixing to obtain mixture B; c) taking the remaining water and mixing it with admixtures to obtain mixture C; d) mixing mixture B, mixture C, and the remaining raw materials for concrete preparation to obtain concrete; in step a), the aggregates include stone and sand, the powder includes tailings ultrafine powder, the admixture includes water-reducing agent, and the remaining raw materials for concrete preparation include cement; by weight, the raw materials for concrete preparation include 150-250 parts of cement. The raw materials for concrete preparation include 790-950 parts of aggregate, 835-980 parts of sand, 280-360 parts of ultrafine tailings powder, 190-270 parts of water, and 20-28 parts of admixtures; the raw materials also include 10-14 parts of borax. The aggregates are modified before being mixed with water to obtain modified aggregates. The modification treatment of the aggregates includes the following steps: according to the weight parts, 12-25 parts of polyvinyl alcohol and 30-46 parts of water are mixed, heated and melted, and then 1.5-2.1 parts of polyethylene glycol, 65-72 parts of water glass with a mass concentration of 5%, and 10-15 parts of organosilicon resin are added and mixed evenly to obtain an aggregate modification liquid; the aggregates are immersed in the aggregate modification liquid, soaked for 40-60 minutes, and then taken out and drained to obtain modified aggregates.

[0004] The above-mentioned concrete production process and concrete improve the utilization rate of admixtures by changing the order of adding aggregates and cement. However, the produced concrete contains a large number of pores, which not only reduces the strength of the concrete, but also makes it easy for rainwater to seep in and corrode the interior of the concrete. Summary of the Invention

[0005] In order to solve the problem that the concrete produced in the prior art contains a large number of pores, the purpose of this invention is to provide a process to improve the performance of concrete, which can reduce the number of pores in the concrete and enhance the strength of the concrete.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows: a process for improving the performance of concrete, comprising the following steps:

[0007] Step 1: Prepare a strong penetrating agent: Mix and stir fluorosilicate, polycarboxylate superplasticizer, complexed soluble calcium salt, alkanolamine reinforcing agent, polyamide solvent, hydrated calcium silicate gel powder and water;

[0008] Step 2: Concrete preparation: The raw materials for concrete preparation include cement, aggregate, fine river sand, slag, microporous corundum balls, alumina powder, dihydrogen phosphate, water, and admixtures; the admixtures include retarders, water-reducing agents, and air-entraining agents; first, mix water with aggregate, fine river sand, and slag, and after the aggregate, fine river sand, slag, and microporous corundum balls have absorbed water and filled, mix cement, alumina powder, dihydrogen phosphate, and admixtures.

[0009] Step 3: Modification with a strong penetrating agent: When using concrete for construction, first apply a layer of concrete, then spray a strong penetrating agent onto the concrete surface.

[0010] The above solution achieves the following beneficial effects: The main causes of porosity in ordinary concrete are: air in the mixture, which forms pores of 25-500 μm under the action of an air-entraining agent; porosity caused by temperature differences during solidification; and porosity caused by insufficient cementitious material due to aggregate bridging. This invention, by including a retarder in the admixture, effectively reduces temperature changes during solidification, allowing sufficient time for the heat generated during solidification to dissipate, thus reducing the probability of porosity formation. Before mixing cement, the aggregate, fine river sand, and slag are soaked to absorb water. Once fully saturated, the admixtures are difficult to penetrate, reducing the absorption of admixtures by the aggregate, fine river sand, and slag, resulting in higher admixture utilization. Soaking fills the aggregate and fine river sand, reducing the probability of bridging and porosity formation.

[0011] After the concrete is coated, a strong penetrating agent is sprayed on it. The strong penetrating agent will penetrate into the concrete along the pores. The CHS gel generated by the hydrated calcium silicate gel powder fills the pores inside the concrete surface and forms a hard shell on the concrete surface, thereby reducing the wear rate and increasing the impact and abrasion resistance. After spraying the penetrating agent, the impact and abrasion resistance of concrete samples with different water-cement ratios increased by 18.9% to 28.3%, the concrete wear rate decreased by 16.0% to 22.4%, and the impact and abrasion resistance of the concrete increased by more than 10%.

[0012] The initial function of slag is primarily a filling effect. Adding appropriately fine slag to concrete enables the compact packing of powder, thereby improving the pore structure, significantly reducing the porosity of the concrete, making it denser, and increasing its strength. As concrete ages and develops pores, rainwater seeps in and dissolves the concrete. The active components of slag, such as SiO2 and Al2O3, react with Ca(OH)2 produced by water erosion in the aquatic environment to form hydrated calcium silicate and hydrated aluminum silicate, thus filling the pores in the concrete.

[0013] The function of microporous corundum spheres is to enhance the rigidity and toughness of concrete. Microporous corundum spheres and alumina powder contain a large amount of Al2O3, which reacts with Ca(OH)2 to form hydrated calcium silicate and hydrated aluminum silicate. This allows concrete colloids to penetrate into the micropores of the microporous corundum spheres, creating a root-like binding force that improves the compactness of the concrete and admixtures. Simultaneously, corundum has a Mohs hardness of 9, making it extremely strong and resistant to torsional shear deformation, thus increasing concrete strength when used as an admixture. Microporous corundum spheres also react with dihydrogen phosphate to form aluminum dihydrogen phosphate, aluminum hydrogen phosphate, and aluminum orthophosphate. Aluminum dihydrogen phosphate has extremely strong adhesive properties, binding aggregates and admixtures together and further enhancing the toughness of the concrete.

[0014] At room temperature and medium temperature, microporous corundum spheres undergo a polymerization reaction with dihydrogen phosphate, which enhances the strength of concrete. At the same time, it does not cause severe dehydration, decomposition, or phase transformation that would lead to structural damage to the concrete. Therefore, the concrete has good heat resistance and maintains good hot strength over a wide temperature range, while its cold strength does not decrease significantly.

[0015] Compared with existing technologies, this method improves the utilization rate of admixtures by reducing the production of concrete pores through the filling of aggregates and fine river sand, while simultaneously spraying a strong penetrating agent after concrete application to strengthen the concrete surface and improve concrete performance. The generated CHS cementitious material penetrates into the concrete to fill pores. By incorporating slag, the powder achieves dense packing, thereby improving the pore structure. Over time, the slag can react with Ca(OH)2 generated by water erosion in an aquatic environment to fill the concrete pores. The use of microporous corundum balls and alumina powder further enhances the strength and toughness of the concrete. At the same time, the microporous corundum balls and alumina powder react with dihydrogen phosphate to enhance the heat resistance of the concrete.

[0016] Furthermore, the strong penetrating agent contains 10%-20% fluorosilicate, 5% polycarboxylate superplasticizer, 5%-10% complexed soluble calcium salt, 1%-2% alkanolamine reinforcing agent, 1%-2% polymeric amide solvent, 0.5%-1.5% hydrated calcium silicate gel powder, and the remainder is water.

[0017] Beneficial effects: The strong penetrating agent produces CSH gel through the volcanic ash effect Ca(OH)2+SiO2+H2O→CSH, which strengthens the concrete by penetrating it. By adjusting the concentration and increasing the water-cement ratio, the effective penetration depth after spraying the strong penetrating agent is increased.

[0018] Furthermore, the proportions of raw materials for concrete preparation are as follows: 100-150 parts cement, 790-950 parts aggregate, 700-750 parts fine river sand, 100-150 parts slag, 100-150 parts microporous corundum balls, 20-25 parts alumina powder, 10-20 parts dihydrogen phosphate, 100-120 parts water, and 20-28 parts admixtures.

[0019] Beneficial effects: Appropriate raw material ratios in concrete preparation can effectively reduce hydration during the concrete setting process, thereby reducing the release of heat of hydration, narrowing the internal and external temperature differences during concrete setting, which helps to reduce the occurrence of internal cracks during concrete setting, improve the structural strength of concrete, and enhance the compressive strength of concrete.

[0020] Furthermore, the small particle size of the stone is 5-20 mm, and the large particle size is 20-40 mm.

[0021] Beneficial effects: Generally, the larger the aggregate size, the greater the concrete strength. However, larger aggregate sizes also create larger voids, resulting in a lower filling rate in the concrete. Therefore, using 20-40mm aggregates to form the framework and 5-20mm aggregates to fill the voids maximizes both strength and filling rate.

[0022] Furthermore, the fineness modulus of the fine river sand is 1.5-2.2.

[0023] Beneficial effects: A small or large fineness modulus, or insufficient gradation, results in poor encapsulation of the stone, easily leading to voids and a lack of density. Selecting appropriate fine river sand can reduce the void rate.

[0024] Furthermore, the concrete curing time is more than 14 days.

[0025] Beneficial effects: Large-volume concrete releases the heat of hydration of cement in a concentrated manner, resulting in rapid internal heating. A large temperature difference between the inside and outside of the concrete can cause temperature cracks, affecting structural safety and normal use. Curing for at least 14 days is recommended to prevent cracking.

[0026] Furthermore, the concentration of the strong penetrant is 14%-15%.

[0027] Beneficial effects: The appropriate concentration of the strong penetrant enhances its penetration performance, resulting in a greater effective penetration depth after spraying. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of an embodiment of the present invention. Detailed Implementation

[0029] The following detailed description illustrates the specific implementation method:

[0030] Example 1

[0031] The basic implementation examples are as follows: Figure 1 As shown:

[0032] A process for improving concrete performance, step one: preparing a strong penetrating agent: mixing and stirring fluorosilicate, polycarboxylate superplasticizer, complexed soluble calcium salt, alkanolamine reinforcing agent, polyamide solvent, hydrated calcium silicate gel powder and water;

[0033] Step 2: Concrete preparation: The raw materials for concrete preparation include cement, aggregate, fine river sand, slag, microporous corundum balls, alumina powder, dihydrogen phosphate, water, and admixtures; the admixtures include retarders, water-reducing agents, and air-entraining agents; first, mix water with aggregate, fine river sand, and slag, and after the aggregate, fine river sand, slag, and microporous corundum balls have absorbed water and filled, mix cement, alumina powder, dihydrogen phosphate, and admixtures.

[0034] Step 3: Modification with a strong penetrating agent: When using concrete for construction, first apply a layer of concrete, then spray a strong penetrating agent onto the concrete surface.

[0035] The specific implementation process is as follows: This invention effectively reduces temperature fluctuations during solidification by including a retarder in the admixture, allowing sufficient time for the heat generated during solidification to dissipate and reducing the probability of porosity formation. Before mixing the cement, the aggregate, fine river sand, and slag are soaked to absorb water. Once fully saturated, the admixtures are less likely to penetrate, reducing the absorption of admixtures by the aggregate, fine river sand, and slag, thus increasing the utilization rate of the admixtures. Soaking also fills the aggregate and fine river sand, reducing the probability of voids in the aggregate and fine river sand, thereby reducing the formation of pores.

[0036] After the concrete is coated, a strong penetrating agent is sprayed on it. The strong penetrating agent will penetrate into the concrete along the pores. The CHS gel generated by the hydrated calcium silicate gel powder fills the pores inside the concrete surface and forms a hard shell on the concrete surface, thereby reducing the wear rate and increasing the impact and abrasion resistance. After spraying the penetrating agent, the impact and abrasion resistance of concrete samples with different water-cement ratios increased by 18.9% to 28.3%, the concrete wear rate decreased by 16.0% to 22.4%, and the impact and abrasion resistance of the concrete increased by more than 10%.

[0037] The initial function of slag is primarily a filling effect. Adding appropriately fine slag to concrete enables the compact packing of powder, thereby improving the pore structure, significantly reducing the porosity of the concrete, making it denser, and increasing its strength. As concrete ages and develops pores, rainwater seeps in and dissolves the concrete. The active components of slag, such as SiO2 and Al2O3, react with Ca(OH)2 produced by water erosion in the aquatic environment to form hydrated calcium silicate and hydrated aluminum silicate, thus filling the pores in the concrete.

[0038] The function of microporous corundum spheres is to enhance the rigidity and toughness of concrete. Microporous corundum spheres and alumina powder contain a large amount of Al2O3, which reacts with Ca(OH)2 to form hydrated calcium silicate and hydrated aluminum silicate. This allows concrete colloids to penetrate into the micropores of the microporous corundum spheres, creating a root-like binding force that improves the compactness of the concrete and admixtures. Simultaneously, corundum has a Mohs hardness of 9, making it extremely strong and resistant to torsional shear deformation, thus increasing concrete strength when used as an admixture. Microporous corundum spheres also react with dihydrogen phosphate to form aluminum dihydrogen phosphate, aluminum hydrogen phosphate, and aluminum orthophosphate. Aluminum dihydrogen phosphate has extremely strong adhesive properties, binding aggregates and admixtures together and further enhancing the toughness of the concrete.

[0039] At room temperature and medium temperature, microporous corundum spheres undergo a polymerization reaction with dihydrogen phosphate, which enhances the strength of concrete. At the same time, it does not cause severe dehydration, decomposition, or phase transformation that would lead to structural damage to the concrete. Therefore, the concrete has good heat resistance and maintains good hot strength over a wide temperature range, while its cold strength does not decrease significantly.

[0040] Example 2

[0041] The difference from the above embodiments is that: the strong penetrant contains 10%-20% fluorosilicate, 5% polycarboxylate superplasticizer, 5%-10% complexed soluble calcium salt, 1%-2% alcohol amine reinforcing agent, 1%-2% polymer amide solvent, 0.5%-1.5% hydrated calcium silicate gel powder, and the remainder is water.

[0042] The specific implementation process is as follows: The strong penetrating agent generates CSH gel through the volcanic ash effect Ca(OH)2+SiO2+H2O→CSH, which strengthens the concrete by penetrating it. By adjusting the concentration appropriately, the water-cement ratio is increased, thereby increasing the effective penetration depth after spraying the strong penetrating agent.

[0043] Example 3

[0044] The difference from the above embodiment is that the raw material ratio for concrete preparation is 100 parts cement, 950 parts stone, 700 parts fine river sand, 100 parts slag, 120 parts water and 20 parts admixture.

[0045] The specific implementation process is as follows: The appropriate ratio of raw materials for concrete preparation can effectively reduce the hydration process during concrete solidification, thereby reducing the release of hydration heat, narrowing the internal and external temperature difference during concrete solidification, which helps to reduce the phenomenon of internal cracks during concrete solidification, improve the structural strength of concrete, and enhance the compressive strength of concrete.

[0046] Example 4

[0047] The difference from the above embodiment is that the small particle size of the stone is 5-20mm, and the large particle size of the stone is 20-40mm.

[0048] The specific implementation process is as follows: Generally, the larger the particle size of the stone, the greater the concrete strength. However, the larger the particle size, the larger the voids, resulting in a lower filling rate in the concrete. Therefore, 20-40mm stone particles form the skeleton, and 5-20mm stone particles are used to fill the voids, maximizing both strength and filling rate.

[0049] Example 5

[0050] The difference from the above embodiment is that the fineness modulus of the fine river sand is 1.5-2.2.

[0051] The specific implementation process is as follows: If the fineness modulus is too small or too large, the gradation is insufficient, and the stone is not well encapsulated, it is easy to cause voids and a lack of density. Selecting a suitable fine river sand fineness can reduce the void rate.

[0052] Example 6

[0053] The difference from the above embodiment is that the concrete curing time is 18 days.

[0054] The specific implementation process is as follows: In large-volume concrete, the heat of hydration from cement is released relatively concentratedly, leading to rapid internal heating. A large temperature difference between the inside and outside of the concrete can cause temperature cracks, affecting structural safety and normal use. Curing for 18 days is necessary to prevent cracking.

[0055] Example 7

[0056] The difference from the above embodiments is that the concentration of the strong penetrant is 14%-15%.

[0057] The specific implementation process is as follows: the concentration of the strong penetrant is appropriate, so that the penetrant has better penetration performance and the effective penetration depth increases after the strong penetrant is sprayed.

[0058] The above descriptions are merely embodiments of the present invention. Commonly known structures and characteristics of the solutions are not described in detail here. Those skilled in the art are aware of all common technical knowledge in the field prior to the application date or priority date, are aware of all existing technologies in that field, and have the ability to apply conventional experimental methods prior to that date. Those skilled in the art can, under the guidance of this application, improve and implement this solution in combination with their own capabilities. Some typical known structures or methods should not be obstacles for those skilled in the art to implement this application. It should be noted that those skilled in the art can make several modifications and improvements without departing from the structure of the present invention. These should also be considered within the scope of protection of the present invention, and will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.

Claims

1. A process for improving the performance of concrete, characterized in that, Includes the following steps: Step 1: Preparation of the strong penetrating agent: Mix fluorosilicate, polycarboxylate superplasticizer, complexed soluble calcium salt, alkanolamine reinforcing agent, polymeramide solvent, hydrated calcium silicate gel powder, and water. The strong penetrating agent comprises 10%-20% fluorosilicate, 5% polycarboxylate superplasticizer, 5%-10% complexed soluble calcium salt, 1%-2% alkanolamine reinforcing agent, 1%-2% polymeramide solvent, 0.5%-1.5% hydrated calcium silicate gel powder, and the remainder is water. Step Two: Concrete Preparation: The raw materials for concrete preparation include cement, aggregate, fine river sand, slag, microporous corundum balls, alumina powder, dihydrogen phosphate, water, and admixtures. Admixtures include retarders, water-reducing agents, and air-entraining agents. First, mix water with the aggregate, fine river sand, and slag. After the aggregate, fine river sand, slag, and microporous corundum balls have absorbed water and filled their contents, mix the cement, alumina powder, dihydrogen phosphate, and admixtures. Before mixing the cement, soak the aggregate, fine river sand, and slag to ensure they are fully saturated with water. Once fully saturated, the admixtures are less likely to penetrate, reducing the water-reducing effect. The absorption of stone, fine river sand, and slag by admixtures improves the utilization rate of admixtures. By soaking, stone and fine river sand are filled, reducing the probability of stone and fine river sand being brittle and reducing the formation of pores. The raw material ratio for concrete preparation is as follows: cement 100-150 parts, stone 790-950 parts, fine river sand 700-750 parts, slag 100-150 parts, microporous corundum balls 100-150 parts, alumina powder 20-25 parts, dihydrogen phosphate 10-20 parts, water 100-120 parts, and admixtures 20-28 parts. Step 3: Modification with a strong penetrating agent: When using concrete for construction, first apply a layer of concrete, then spray a strong penetrating agent onto the concrete surface.

2. The process for improving concrete performance according to claim 1, characterized in that: The small particle size of the stone is 5-20 mm, and the large particle size is 20-40 mm.

3. The process for improving concrete performance according to claim 2, characterized in that: The fineness modulus of fine river sand is 1.5-2.

2.

4. The process for improving concrete performance according to claim 3, characterized in that: The concrete curing time is more than 14 days.

5. The process for improving concrete performance according to claim 4, characterized in that: The concentration of the strong penetrant is 14%-15%.

Citation Information

Patent Citations

  • A concrete production process and concrete

    CN110156389B

  • Concrete surface reinforcing agent and using method thereof

    CN108975952A